LITERATURE REVIEW: ANALYSIS OF HOSPITAL READINESS IN FACING STANDARD INPATIENT CLASS (KRIS) - Sidiq Himawan, Noor Syam (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2024)
The Indonesian government introduced the National Health Insurance (JKN) program to ensure basic health coverage for its citizens. However, challenges emerged during its implementation, including difficulties in accessing adequate healthcare services. To address this, the Standard Inpatient Class (KRIS) concept was introduced in select Indonesian hospitals, aiming to deliver equitable services by standardizing rates and quality of care. This narrative literature review assesses the readiness of various hospitals in adopting KRIS. A search was conducted using Google Scholar, ScienceDirect, and PubMed with keywords related to hospital readiness for KRIS policy. Screening using the PRISMA method resulted in the inclusion of 4 out of 15 articles. Findings reveal variations in hospital preparedness, with Hospital A, B, C, and D demonstrating readiness levels of 75%, 74%, 75%, and 70%, respectively. Hospital A excelled in criteria 6 and 7 (95%), while struggling in criterion 1 (64%). Hospital B demonstrated strong readiness in criterion 7 (85%) but lacked in criterion 8 (49%). Hospital C performed well in criterion 5 (90%) but poorly in criterion 11 (34%). Hospital D exhibited high readiness in criterion 3 (88%) but lacked in criterion 4 (50%). On average, hospitals displayed 73% readiness, with criterion 3 (87%) achieving the highest readiness, particularly in room lighting, while criterion 4 (55%) showed the lowest readiness, specifically in bed completeness. These findings underscore the need for further improvements to enhance hospital readiness for KRIS implementation.